Media wobec ucznia, uczeń wobec mediów - Błażejewska, Joanna; Kaźmierczak, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
In the present article, the influence of media on students as well as on school education is discussed. The article shows the most important objectives and challenges for the present media education and indications concerning the introduction of the student into the world of media culture.